2013
DOI: 10.1007/s12645-013-0040-9
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of gold nanoparticles and their anticancer activity

Abstract: As the nano revolution unfolds, it is imperative to integrate nanoscience and medicine. The secret gleaned from nature have led to the generation of biogenic technologies for the fabrication of advanced nanomaterials. Present investigation discloses the gold nanoparticles biosynthesizing capability of the flower of pharmacologically important tree Couroupita guianensis. Rapid, cost-effective, one-step process of synthesis has been achieved. Newly genre gold nanoparticles were characterized by involving UV–vis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(73 citation statements)
references
References 31 publications
5
68
0
Order By: Relevance
“…Depending upon size, Coccinia, Caesalpenia pulcherrima (linn) [17] and Plumeria alba linn [18]. AuNPs synthesized using plant extracts as reducing agent are used in applications like anticancer activities [16], antimicrobial activities [17,18] and catalytic activities for the reduction reaction of 4-Nitrophenol [13] and H 2 O 2 [15]. This paper reports the room temperature synthesis of stable AuNPs using Mimosa pudica flower extract as reducing agent.…”
Section: Uv-vis Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending upon size, Coccinia, Caesalpenia pulcherrima (linn) [17] and Plumeria alba linn [18]. AuNPs synthesized using plant extracts as reducing agent are used in applications like anticancer activities [16], antimicrobial activities [17,18] and catalytic activities for the reduction reaction of 4-Nitrophenol [13] and H 2 O 2 [15]. This paper reports the room temperature synthesis of stable AuNPs using Mimosa pudica flower extract as reducing agent.…”
Section: Uv-vis Studiesmentioning
confidence: 99%
“…AuNPs were synthesized by heating the mixture of gold precursor solution and extracts of flowers like Nyctanthes arbortristis, Achillea wilhelmssi, Gnidea glauca [13], Lonicera japonica [14] and Allamanda [15]. Room temperature synthesis of AuNP was reported by mixing the gold precursor solution and aqueous extract of flowers like Rosa hybrida [11], Mirabilis jalapa [13], Rosa damascena [15] and Couroupita guianensis [16]. Incubation of gold precursor solution and aqueous flower extract for few hours yielding AuNPs was reported using flowers like Ixora…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the ability of AgNPs and AuNPs to induce apoptosis. 26,36 We evaluated the ability of D-AgNPs alone or in combination with CK to induce cellular apoptosis based on Hoechst 33258 staining. We found that D-AgNPs alone induced changes in the nuclear morphology of many cells at 50 µg/mL, but combination treatment with 50 µg/mL of D-AgNPs with 25 µM of CK exhibited even more apoptotic bodies.…”
Section: D-agnps and D-aunps Induce Apoptosis In A549 Cellsmentioning
confidence: 99%
“…Dextran is readily soluble in water and electrolytes with excellent stability and it has wide range of use in food, medical related areas, and biological functions, especially for blood flow improvement by reduction of blood viscosity and inhibition of erythrocyte aggregation [30,31]. Therefore, dextran stabilized AuNPs are promising to use for intravenous administration as X-ray contrast agent [16,32], cancer therapy [33,34] including photothermal cancer therapy [35,36], and for other purposes of application as well [23].…”
Section: Introductionmentioning
confidence: 99%